Identification and sequence analysis of the gene mutated in the conditionally lethal outer membrane permeability mutant SS-C of Salmonella typhimurium. - Hirvas, L (1991)
The biosynthesis and structure-function relationships of the enterobacterial outer membrane are subjects of current intensive research. We have previously described the antibiotic supersensitive SS-C mutant (SH7622) of Salmonella typhimurium and shown that its outer membrane permeability barrier against hydrophobic antibiotics is severely defective. In this study, we show that this mutant is heat-sensitive, conditionally lethal, and carries a missense base-pair substitution in a novel gene which we have recently reported and now named the ssc gene. ssc encodes an earlier uncharacterized 36 kd protein (the Ssc protein) and the mutant expresses Ssc which has valine 291 changed to methionine in a methionine-rich region of Ssc. A plasmid containing the wild-type ssc allele completely reverts the antibiotic- and heat-sensitive phenotype of the SS-C mutant. Corresponding plasmids carrying the mutant allele, or an identical mutant allele prepared by localized mutagenesis, are inactive. The ssc gene is probably analogous to the firA locus of Escherichia coli which has earlier been implicated in a totally different function, mRNA synthesis. Furthermore, ssc apparently lies very close to the lpx genes involved in the thus far known steps of lipid A biosynthesis (the distance, approximately 560 bp). To conclude, our findings define a new essential gene involved in the generation of the outer membrane.